GAMBARAN KEANEKARAGAMAN KONSUMSI PANGAN IBU HAMIL DI WILAYAH KERJA PUSKESMAS MAROBO KABUPATEN MUNA - Mochtar, Febriana; Hayulia, Wa Ode Nurul; Octaviani, Rizki Eka Sakti (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
The nutritional intake of pregnant women is a critical factor that supports the fetal growth and physiological requirements during the pregnancy. Adequate nutrition can be fulfilled by consuming diversified diet. This research was performed to assess the diversity of dietary intake among pregnant women in Marobo Public Health Center, Muna Regency, in 2024. This quantitative research was carried out using a descriptive observational design, involving 64 pregnant women selected using proportional sampling technique. The data of this research were gathered through interviews and questionnaires, including data on maternal age, gestational age, and dietary diversity. A 24-hour recall method and the Minimum Dietary Diversity for Women (MDD-W) were employed to assess the food diversity. The findings revealed that 50 participants (78.1%) had non-diverse diets, while 14 participants (21.9%) consumed a diverse range of foods. The diversified dietary intake among pregnant women should be enhanced in order to ensure adequate nutritional intake.